Hubungan Pola Asuh Orang Tua dengan Kemampuan Berpikir Logis Anak Usia Dini - Siti Nur Azkiah I. Hulawa; Elva M. Sumirat; Esperansa Mile; Alia Azizah Sapii (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research is motivated by the importance of the relationship between parenting styles and the logical thinking skills of early childhood. The development of logical thinking is part of the cognitive aspect that plays a role in children's ability to solve problems, understand cause-and-effect relationships, and make decisions. This study aims to determine the most effective parenting style in improving children's logical thinking skills. The study used a quantitative approach with a correlational method and was conducted at the KB Mekar Indah Early Childhood Education Center (PAUD). Data were obtained through observation, interviews, and tests with 15 respondents. The results showed a significant relationship between parenting styles and the logical thinking skills of early childhood. Democratic parenting styles have the most positive influencThis research is motivated by the importance of the relationship between parenting styles and the logical thinking skills of early childhood. The development of logical thinking is part of the cognitive aspect that plays a role in children's ability to solve problems, understand cause-and-effect relationships, and make decisions. This study aims to determine the most effective parenting style in improving children's logical thinking skills. The study used a quantitative approach with a correlational method and was conducted at the KB Mekar Indah Early Childhood Education Center (PAUD). Data were obtained through observation, interviews, and tests with 15 respondents. The results showed a significant relationship between parenting styles and the logical thinking skills of early childhood. Democratic parenting styles have the most positive influence compared to permissive and authoritarian parenting styles, as shown by higher logical thinking scores in children. Thus, democratic parenting styles are recommended to be implemented to support children's cognitive development.e compared to permissive and authoritarian parenting styles, as shown by higher logical thinking scores in children. Thus, democratic parenting styles are recommended to be implemented to support children's cognitive development.